The impact of driver's license ownership on unemployed job seekers' access to job openings: Assessing the driver's license at School project in Flanders. Issue 4 (December 2018) - Fransen, Koos; Deruyter, Greet; De Maeyer, Philippe
Highlights: Connecting disadvantaged individuals to jobs is vital for social inclusion strategies. The discontinuation of the Driver's License at School project was assessed. Driver's license ownership and education level strongly impact job accessibility. Disadvantaged job seekers have access to less opportunities. Transport, planning and labor policies should address issues of transport inequity. Abstract: An inefficient accessibility to the labor market is considered as one of the key threats to a region's economic wellbeing. However, the high dominance of and independency on travel by private motorized vehicle related to the post-war emergence of the automobile industry has led to various spatial mismatches between living locations and the labor market. Consequently, unemployed job seekers' inability to find a suitable job is strongly interwoven with transport-related issues, and more specifically, with having a driver's license. The research aims to examine the impact of the policy decision to discontinue the 'Driver's License at School' project, which currently provides secondary school pupils (aged 17 years or older) with the ability to obtain their theoretical driver's license at a diminished rate. This is examined through the assessment of job seeker's accessibility to job vacancies in the region of Flanders (and, in extension, the Brussels Capital Region). Therefore, a spatio-temporal accessibility measure was constructed to identify the number of job opportunities per traffic analysis zone for different transport modes, while considering job competition. The results show that job seekers with a driver's license have a higher accessibility to job opportunities than those without. Moreover, significant relationships exist between job seekers' accessibility and their socio-demographic characteristics. The study argues that – although laudable from an environmental perspective – the discontinuation of the project will lead to various inequitable outcomes for certain groups. This has important ramifications for transport policies focusing on equity in job accessibility as well as spatial planning policies that address how the future Flemish urban landscape should ideally evolve. In addition, it fuels the debate on the discrepancy between sustainable transport policies and an equitable distribution of transport benefits.